Determinan Perceraian di Jakarta Timur Tahun 2014 (Studi Data Pengadilan Agama dan Pengadilan Negeri) (Faculty of Social Science, Universitas Negeri Semarang, 2019)
The amount of divorces in Jakarta contributes to high divorce in Indonesia. East Jakarta is a city with an increasing amount of divorces from 2010-2014 and has the highest amount in Jakarta in 2014.Â Research on divorce was analyzed by considering the duration until divorce occurred, so Survival Analysis was used to determine demographic and socio-economic variables that influenced divorce.Data sourced from the 2014 archive of the Religious Courts and East Jakarta District Courts. The results of the analysis using Weibull Regression with 5% significance, variables that are at high risk in East Jakarta are couples who do not have children at their marriage, the gap of age at least 5 years, wife and husbands who worked, and the reasons for domestic violence, irresponsibility, family disharmony and economic problems alsoÂ positively affected the risk of divorce in East Jakarta in 2014.